Letter - General Strike Committee, Ashford, 11 May 1926 (Ashford)
1926-05-11 "Letter - General Strike Committee, Ashford, 11 May 1926" [g0301001.jpg], 11 May 1926, General Strike Committee, Ashford, Northfield, W. Local Organisation